Comparative Study of Adipose-Derived Stem Cells From Abdomen and Breast - Guneta, Vipra (2017)
Background: Abdominal tissue enriched with adipose-derived stem cells (ASCs) is often used in cell-assisted lipotransfer procedures for breast reconstruction. However, as the tissue microenvironment and stem cell niche play important roles in defining the characteristics of the resident cells, it is hypothesized that the stem cell population present in the donor abdominal tissue has dissimilar properties as compared with the cells in the recipient breast tissue, which may ultimately affect the long-term success of the graft. Methods: Adipose-derived stem cells were isolated from breast and abdominal fat tissues and characterized for mesenchymal-specific cell surface markers, and their population doubling, colony-forming capabilities, and proliferative properties were compared. The multilineage potential of both cell populations was also investigated. Results: Adipose-derived stem cells from both tissue sites were found to possess similar marker expression and multilineage differentiation potential. However, breast fat–derived ASCs were observed to have a higher self-renewal capability and an unstable population doubling as compared with abdominal fat-derived ASCs. Gene expression studies revealed that the breast fat–derived ASCs were predisposed to the osteogenic lineage and the abdominal fat–derived ASCs to the adipogenic lineage. Conclusions: Cells derived from both fat tissues possess different characteristics in terms of their growth kinetics and predisposition to the osteolineages and adipolineages. In particular, ASCs from the abdominal tissue appear to contribute to adipose tissue turnover, whereas ASCs from breast tissue, if used for cell-assisted fat grafting, may potentially be responsible for complications in fat grafting, such as oil cysts, calcifications, fat necrosis, and tumors.